Problems of jurisdictional dispersion in the European private international family law - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
In this paper are analyzed the formulas that have been used in the European regulation of family law to avoid the jurisdictional dispersion: from article 10 Regulation 2019/1111 (accumulation of parental responsibility to the forum divortii, provided that the parental responsibility accept); the article 3 item c) and (d)) Regulation 4/2009 that it provide for an concentration without giving entrance to the party autonomy o the articles 4 and 5 of the recent regulations on matrimonial economic regimes and patrimonial effects of the registered unions, respectively, where a decisive role is given to the autonomy on issues related to the marital crisis and the annulment or dissolution of registered unions , against non-operation of the party autonomy if the main issue is succession.
Keywords: Jurisdiction; jurisdictional dispersion; party autonomy; accesory questions; jurisdictional concentration